2021
DOI: 10.1038/s41398-021-01471-y
|View full text |Cite
|
Sign up to set email alerts
|

Genome wide study of tardive dyskinesia in schizophrenia

Abstract: Tardive dyskinesia (TD) is a severe condition characterized by repetitive involuntary movement of orofacial regions and extremities. Patients treated with antipsychotics typically present with TD symptomatology. Here, we conducted the largest GWAS of TD to date, by meta-analyzing samples of East-Asian, European, and African American ancestry, followed by analyses of biological pathways and polygenic risk with related phenotypes. We identified a novel locus and three suggestive loci, implicating immune-related … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…Although commonly observed in patients with schizophrenia, tardive dyskinesia can occur in individuals with other psychiatric disorders. Single-nucleotide polymorphisms in CALCOCO1 appear to confer threefold increase in tardive dyskinesia risk ( 489 ). Single-nucleotide polymorphisms in CALCOCO1 have also been associated with panic disorder, an anxiety disorder characterized by panic attacks and anticipatory anxiety ( 490 ).…”
Section: Lysosomal Clearance Of the Er And Related Human Diseasesmentioning
confidence: 99%
“…Although commonly observed in patients with schizophrenia, tardive dyskinesia can occur in individuals with other psychiatric disorders. Single-nucleotide polymorphisms in CALCOCO1 appear to confer threefold increase in tardive dyskinesia risk ( 489 ). Single-nucleotide polymorphisms in CALCOCO1 have also been associated with panic disorder, an anxiety disorder characterized by panic attacks and anticipatory anxiety ( 490 ).…”
Section: Lysosomal Clearance Of the Er And Related Human Diseasesmentioning
confidence: 99%
“…To investigate the genetic variability of the potential underlying mechanisms and pathways of TD, they applied a robust and thorough bioinformatic analysis, including meta-analysis, functional annotation, eQTLs, transcriptome-wide fine-mapping, polygenic risk score analyses and multivariate logistic regression analyses. The study revealed the importance of three genomic loci on chromosomes 1, 6 and 12 and a novel locus on chromosome 16, highlighting the importance of TNFRSF1B, EPB41L2, CALCOCO1 and GSE1 genes ( Lim et al, 2021 ). TNFRSF1B is a member of the tumor necrosis factor receptor superfamily and participates in the antiapoptotic signaling pathway.…”
Section: Genome-wide Association Studies Of Tardive Dyskinesiamentioning
confidence: 95%
“…TNFRSF1B is a member of the tumor necrosis factor receptor superfamily and participates in the antiapoptotic signaling pathway. It is expressed in immune cells, highlighting the importance of immune system in TD pathogenesis ( Lee and Kang 2011 ; Lanning et al, 2016 ; Lim et al, 2021 ). EPB41L2 is a membrane protein that was found to have a protective effect on motor activity.…”
Section: Genome-wide Association Studies Of Tardive Dyskinesiamentioning
confidence: 99%
See 1 more Smart Citation
“…GRIN2B is located on chromosome 12p12 and codes for a polypeptide of 1484 amino acid residues, GluN2B or NR2B [ 25 ]. These genes have been investigated for possible involvement in the pathophysiology of TD in patients with schizophrenia, but the results of the studies are inconsistent [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%